PENGGUNAAN BEBERAPA JENIS SUMBER ASAP CAIR DAN PENGARUHNYA TERHADAP AROMA SERTA CITA RASA DAGING SEI (PROSES PRODUKSI ALTERNATIF DAGING SEI UNTUK KEAMANAN PANGAN) - Max A.J. Supit; Anna Daulima; Bachtaruddin Badewi (Partner, 2013)
Application of Various Liquid Smokes and Their Effects on Aroma and Flavour of The Sei Meat (An Alternative Production Process of The Sei Meat for Food Safety). The sei meat were treated with 3 kinds of liquid smoke (kesambi, coconut shell, and palmyra shell) to resemble the aroma and flavour of the traditional sei meat. Liquid smokes were diluted to 2% then employed to marinate samples for 15 minutes before the sample were cooked in the conventional oven (heated by kerosene stove). 22 panelists examined the aroma and flavours of sampels which were disigned by using Difference from Control Test. Resulted data were analysed by using ANOVA and Least Significant Difference by employing SPPS for windows version 16 software.The results of statistical analysis showed that there were significant differences existed in both the aroma and flavour of the treatments (Î±=0,001). Similarly, post test analysis results showed that there were significant differences between the control (and blind control) samples and all liquid smoke treated samples but no difference among the latters. Furthermore, the control (and blind control) samples were able to be distingushed from all liquid smoked treated samples. Therefore, in general, the sei meats produced by using 3 different kinds of liquid smoke have not resemble the aroma and flavour characters of the traditional sei meat yet. Keywords: Sei Meat, Liquid Smoke, Kesambi, Coconut Shell, Palmyra Shell